Energizers : Classroom-based Physical Activities K-2 - Mahar, Matthew T.; Kenny, Rhonda K.; Shields, A. Tamlyn; Scales, Donna P.; Collins, Gretchen (My University, 2006)
Energizers Energizers are classroom-based physical activities that were designed to help teachers integrate physical activity with academic concepts. The energizers were developed by a team from the Activity Promotion Laboratory at East Carolina University. Teachers can download these activities free of charge and are encouraged to incorporate these activities into their classroom. Our research, published in the journal Medicine and Science in Sports and Exercise (2006, volume 38, number 12), demonstrated that: (a) Energizers are easy to implement; (b) both teachers and students enjoy the Energizers activities; (c) use of Energizers activities improves on-task behavior of students; and (d) use of Energizers increases the amount of physical activity accumulated over the course of the school day.
Keywords: Energizers; Exercise; Kindergarten; First Grade; Second Grade; active